The Impact of Macroeconomic Variables on IHSG and JII: An ARDL Approach - Dito Prakoso (SMART Insight, 2022)
The Islamic capital market plays an important role in the growth of the economy in Indonesia. During its development, the performance of the stock index in a country is often influenced by other stock indices in other countries. This study tries to analyze dependance of macroeconomic variable towards Jakarta Islamic Index (JII) and Indonesia Composite Index (IHSG), using Autoregression Distributed Lag (ARDL). The results show that in a short term, the US S&P 500 and Singapore STI price index significantly affect both of the JII and IHSG price index. Also, the exchange rate and crude oil price significantly affect the JII and IHSG, respectively. In a long term, the money supply, exchange rate and Singapore STI price index significantly affect the IHSG.